Assessment of Biochemical Potential of Rhizopus oligosporus as Starter Culture to Enhance the Nutritional Value of Palm Kernel Cake for Animal Feed Formulation - F. O. Uche; E. O. Egbune; A. A. Anigboro; N. J. Tonukari (Journal of Applied Sciences and Environmental Management, 2024)
The objective of this study was to assess the biochemical potential of Rhizopus oligosporus as a starter culture to enhance the nutritional value of palm kernel cake (PKC) for animal feed formulation using appropriate standard methods. Among the experimental groups, the batch of birds fed with solid-state fermented PKC as a 50% maize replacement showed a noteworthy weight gain (p < 0.05) in relation to the control group, while the other experimental groups exhibited a weight loss. Serum levels of ALT, AST, ALP, creatinine, and blood urea did not show a notable difference from the reference group and those on the experimental diets. These findings collectively suggest that the pre-treatment of PKC using R. oligosporus holds the potential to elevate its nutritional quality for utilization in animal feed applications.